Recent update on the prevalence of Vibrio species among cultured grouper in Peninsular Malaysia - Nor Zulkiply, Amalina; Zulperi, Dzarifah; Azmai, Mohammad Noor Amal; Yusof, Mohd Termizi; Saad, Mohd Zamri; Al-Saari, Nurhidayu; Tanaka, Mami; Mino, Sayaka; Sawabe, Tomoo; Md Yasin, Ina Salwany (Wiley, 2019)
Vibrio infections are common among marine fish and lead to serious problems in the aquaculture sector. This study reports a recent occurrence of Vibrio species (spp.) isolated from cultured groupers in Peninsular Malaysia using the gyrB and pyrH genes. A total of 147 Vibrio strains were successfully isolated from 77 (64%) groupers using culture method and subjected to gyrB and pyrH sequencing for species identification and confirmation. Results showed that 89% of Vibrio strains were identified and clustered to six groups of Vibrio spp., while 11% were not clustered to any Vibrio spp. using the gyrB sequences. Meanwhile, by analysis of the pyrH sequences all the 147 Vibrio strains (100%) were successfully identified and clustered into 11 groups of Vibrio spp., including the gyrB non‐identified strains. The pyrH gene provides a better resolution for identification of Vibrio spp. compared with the gyrB gene. Thus, the pyrH gene was more suitable for a rapid determination of Vibrio spp. distribution in Peninsular Malaysia. Using the pyrH gene, our study found higher prevalence of Vibrio vulnificus (33%), V. alginolyticus (24%) and V. parahaemolyticus (22%), followed by V. rotiferianus (5%), V. harveyi (3%), V. tubiashii (2%), V. campbellii (2%), V. ponticus (1%), V. diabolicus (1%), V. owensii (1%) and others Vibrio sp. (7%). Thus, the results of this study revealed that the occurrence of pathogenic vibrios among grouper fish is still high in Malaysian aquaculture. In addition, the pyrH gene was proved as a suitable marker for rapid identification of Vibrio species compared with the gyrB gene.